Respuesta :

According to table : [tex]a_1= -1.[/tex]

[tex]a_2= 1[/tex]

[tex]a_3= 3[/tex]

[tex]a_4=5[/tex].

Now, we can find common difference, : second term - first term =  1-(-1) = 1+1=2.

We know formula for a recursive sequance of an arithmetic sequence is

[tex]a_n=a_{n-1}+d[/tex], where n is the number of term and d is the common difference.

If we plug d=2 in that formula, we would get

[tex]a_n=a_{n-1}+2.[/tex]

Therefore, correct option is second [tex]a_n=a_{n-1}+2[/tex] option.


ACCESS MORE